2001
DOI: 10.1557/proc-695-l6.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Porosity of Organo-Silicate Glass (OSG) Low-k Dielectric Films

Abstract: Low-k material integration issues that plague the microelectronics industry include the compromise in mechanical properties that one incurs in abandoning fully dense silica dieletrics. Typical elastic moduli of OSG low-k dieletric films are 2-10 GPa with corresponding hardnesses of 0.5 to 1.5 GPa. In the present study, the hardness and elastic modulus properties measured by nanoindentation of porous silica based low-k films are correlated with in initial estimates of density using a novel technique of spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Comparison to other literature values for hardness of CVD organosilicon-type films shows that the high-power V 3 D 3 sample compares favorably in terms of hardness ͑1.3 GPa͒ vs. dielectric constant (3.0 Ϯ 0.1). Vella et al 31,32 reports hardness values for CVD OSG films in the range of 1.2-2.0 GPa, while Grill et al 27 report a dense OSG hardness of approximately 1.7 GPa for a dielectric constant of 2.8. Lu et al 30 describe an OSG system with a hardness of 2.4 GPa for a dielectric constant of 2.7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison to other literature values for hardness of CVD organosilicon-type films shows that the high-power V 3 D 3 sample compares favorably in terms of hardness ͑1.3 GPa͒ vs. dielectric constant (3.0 Ϯ 0.1). Vella et al 31,32 reports hardness values for CVD OSG films in the range of 1.2-2.0 GPa, while Grill et al 27 report a dense OSG hardness of approximately 1.7 GPa for a dielectric constant of 2.8. Lu et al 30 describe an OSG system with a hardness of 2.4 GPa for a dielectric constant of 2.7.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Some mechanical property data exists for these systems as well. 27,[30][31][32] From a semiconductor processing standpoint, it is convenient to envision using an all-CVD process vs. a spin-on process to fabricate a porous thin film, due to the numerous advantages CVD processing allows, including seamless compatibility with existing toolsets, lower environmental impact, and less solvent/ material waste. 33 However, the PECVD matrix-porogen route has proved to be a difficult one.…”
mentioning
confidence: 99%
“…Spectroscopic ellipsometry performed on these films showed a substantial difference in refractive index, which given chemical similarity, suggest difference in relative electron density or porosity (Fig. 1b) [19,20]. While exploring the process space of this new tool, including reaction temperature, partial pressures of inert and reactant gases, films of varying mechanical properties were generated.…”
Section: Resultsmentioning
confidence: 99%
“…Since fracture toughness strongly depends on the flaw size, preliminary measurements of low-k relative electron density/ porosity with spectroscopic ellipsometry have been made [20], but at this point more thorough theoretical analysis is required to accurately assess thin film fracture toughness using the nanoindentation technique in order to correlate the two types of measurements.…”
Section: Figure 4 Typical Indentation-induced Blister and Its Fib Crmentioning
confidence: 99%
“…Despite such a large difference in mechanical properties, the films appeared virtually identical when compared by XPS and also by TEM cross-section. 31 Accordingly, spectroscopic ellipsometry (SE) was performed to see if any difference that could explain between the two sets of films could be observed that would explain the unusual differences in mechanical properties. We have argued that ellipsometry is sensitive to electron density and thus to local structural arrangement; therefore, differences in crystal structure, interface and surface properties, stoichiometry and relative porosity, if present, should manifest themselves in the optical data.…”
Section: Critical Issues For Low-k Materialsmentioning
confidence: 99%